Guide to Selection of Adult Literacy Materials. Analyze before You Buy - Darling, Sharon; Jefferson County Public Schools, Louisville, KY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
This guide, one in a series of works dealing with adult literacy education, is designed to help adult reading program staff to select adult literacy materials. Examined in the first section of the guide are the commercially prepared basal and supplemental reading materials that are available for use in the Jefferson County Adult Reading Program (JCARP) in Louisville, Kentucky. The second section contains general criteria for evaluating reading materials and a guide for determining readability levels of published materials. Provided in the third section is a descriptive listing of other sources that contain bibliographies of adult literacy materials for student and professional use. An overview of some common instructional approaches for teaching reading to adults (language experience, individualized reading, linguistic, programmed reading, modified alphabet, machine presented, diagnostic-prescriptive and eclectic approaches) is appended to the guide. (MN)
Availability: Jefferson County Adult Education, 4409 Preston Highway, Louisville, KY 40213 ($3.00).
ERIC Note: For related documents, see CE 037 069-072.
Educational level discussed: Adult Basic Education.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Basic Education; Adult Literacy; Adult Reading Programs; Annotated Bibliographies; Basal Reading; Classroom Techniques; Evaluation Criteria; Guidelines; Instructional Materials; Literacy Education; Media Selection; Readability; Reading Instruction; Reading Materials; Reading Skills; Supplementary Reading Materials; Teaching Methods; Textbook Evaluation; Textbook Selection; Jefferson County Adult Reading Program KY; 310 Project; Guides, General; Reference Materials, Bibliographies